The Role of Hypertonic Saline in Ablative Radiofrequency of the Sacroiliac Joint: Observational Study of 40 Patients - Ezio Amorizzo; Gianni Colini-Baldeschi (Clinics and Practice, 2022)
Background: The aim of this retrospective uncontrolled article is to illustrate a technique of neurotomy of the sensitive branches of S1 S2 S3 in RFA that appears to result in a better success rate and longer-lasting pain relief. Methods: 40 patients were treated, 26 females and 14 males, with an average age of 74 (92–55). After the examination, the patients underwent an ultrasound-guided diagnostic block of the affected sacroiliac joint. Only patients who presented pain relief greater than 60% after the diagnostic block were candidates for the RFA procedure. The procedure was always performed in the operating room on an outpatient basis. After obtaining the best fluoroscopic visualization of the joint to be treated, two RFA cannulae were placed starting from the lower medial margin parallel to the SIJ to perform a bipolar RFA along the entire medial margin of the SIJ. Lidocaine 2% and hypertonic saline 2 mEq/mL were used for each RFA level. Patients were followed-up at 3, 6, 12, 18, and 24 months by evaluating the NRS and SF-12. Results: Patients reported extreme satisfaction with the procedure performed and reported a significant improvement in NRS and SF-12 at FU visits. No adverse events occurred. Conclusions: Bipolar RFA treatment of the sacroiliac joint with the use of a hypertonic saline solution appears to improve the success of the method and its durability. We are inclined to believe that the use of hypertonic saline may significantly increase the lesion area and result in a greater effect on the sensory branches.